Best Exercises for Off-Season Volleybal - VanLaningham, J.; Alejo, B.
Here are Coach Alejo's most highly recommended exercises for volleyball players to focus on during the off-season. There are two factors that can determine how good a volleyball player can become. One factor is the physical condition that the individual player is in, and the other factor is the level of skill the player possesses. Although it is a good idea to work on both factors year around in order to improve, the off-season is the ideal time to really buckle down and get into the best shape possible. The first thing the author mentioned is that it's a good idea to break the program into three categories: 1) Resistance Training, 2) Plyometrics, and 3) Cardiovascular Training.